BIRDS EYE 6-69, 5-17 September 1969. - Freeman, R. F.; Rankin, R. D. (1970)
BIRDS EYE 6-69 was a regularly scheduled Arctic Ocean ice reconnaissance mission covering the Canadian Archipelago, Baffin Bay, and the area west of Banks Island from 5 to 17 September 1969. Ice observations contained in this report were made under daylight conditions. Weather conditions were excellent west of Banks Island and throughout Parry Channel; conditions elsewhere varied from poor to good. Remnant ice in Baffin Bay exceeded extreme conditions depicted in H.O. Publication 705 (Oceanographic Atlas of the Polar Seas). Parry Channel was ice free from Baffin Bay to near Resolute; however, icebergs existed in eastern Lancaster Sound. Seven to eight oktas of heavily puddled ice existed in Viscount Melville Sound and M'Clure Strait with some refreezing. Lesser conccentrations occurred within 30 nautical miles of Prince of Wales Strait. Shelf ice fragments were sighted within the pack ice. The icebreaking tanker SS Manhattan was located near 74 deg 36 min N, 104 deg 30 min W. Ice data from special flights made in April and May are included. Ice data obtained in the Canadian Archipelago and Polar Basin areas during April and May 1969 are also included. (Author)